The Effect of Green Bonds on Natural Capital Protection: Worldwide Evidence - Tamula, Keziah Eunice; Navidad, Nazh Claire; Peregrino, Trishia Dianne; Abing, Martha Joy Jalalon; Teves, Maria Rizalia; Capulong, Charlyn; Laygan, Resa Mae (Universitas Muhammadiyah Yogyakarta, 2024)
The continued destruction of nature, including the degradation of natural capital and biodiversity, threatens ecosystem services and human well-being. Natural capital is crucial for providing the conditions necessary for human survival and ecosystem services. Without protecting natural capital, this degradation will have lasting effects on current and future generations. Existing studies increasingly show that Green Bonds can finance environmental projects effectively, but few have examined their impact on natural capital protection. This study investigates the effect of Green Bonds on natural capital protection globally, using IMF Climate Data and World Bank data from 2019 to 2022. By applying the Green Investment theory and quantile-panel regression analysis, the results show that Green Bonds significantly enhance natural capital protection at the 25th and 50th percentiles. This indicates that countries can improve their natural capital protection through the issuance of Green Bonds. Moreover, the study finds that renewable energy positively correlates with natural capital protection, while population growth and total natural resource rents have negative impacts. Hence, this study recommends that governments prioritize the issuance of Green Bonds to fund environmental initiatives.